Diversity and Potential Cross-Species Transmission of Rotavirus A in Wild Animals in Yunnan, China - Xiang Le; Yinzhu Tao; Binghui Wang; Yutong Hou; Yuting Ning; Junjie Hou; Ruimei Wang; Qian Li; Xueshan Xia (Microorganisms)
Rotavirus A (RVA) is the primary enteric pathogen of humans and many other species. However, RVA interspecies transmission remains poorly understood. In this study, we conducted a comprehensive screening and genotyping analysis of RVA in 1706 wild animal samples collected from various regions within Yunnan Province, China. A total of 24 samples, originating from wild boars, rodents, bats, and birds tested positive for RVA. Next generation sequencing and phylogenetic analyses revealed a high degree of genetic diversity and reassortment, particularly for VP4 and VP7. Strains isolated from wild boars and rodents exhibited gene segments with high similarity to those found in humans and other mammalian RVA strains, indicating that RVA may undergo interspecies transmission and reassortment, resulting in novel strains with potential risks for human infection. This study provides critical data for understanding the transmission mechanisms and the RVA host range, and highlights the pivotal role of wildlife in viral evolution and dissemination. These findings have significant implications for public health policies and emphasize the need for enhanced surveillance to prevent interspecies RVA transmission.